Budget impact analysis of the use of daclatasvir in Italy for the treatment of Hepatitis C Virus (HCV) genotype 3 patients - Restelli, Umberto; Alberti, Alfredo; Lazzarin, Adriano; Bonfanti, Marzia; Nappi, Carmela; Croce, Davide (Farmeconomia. Health Economics and Therapeutic Pathways, 2016)
BACKGROUND: Hepatitis C Virus (HCV) infection represents a global health problem, leading to chronic cirrhosis, hepatocellular carcinoma (HCC), hepatic decompensation and liver transplant. The aim of the study was the evaluation of the impact on the budget of the Italian National Health Service (INHS) of the use of Daclatasvir (DCV) for the treatment of HCV genotype 3 in patients with advanced fibrosis. METHODS: An analytical decision model with a five year time horizon was implemented. Two scenarios were considered: a. 100% of market share for Interferon (INF-α)+Ribavirin (RBV)+Sofosbuvir (SOF) for 12 weeks; b. SOF+DCV+RBV for 24 weeks with annual market shares of 50% in 2015 and 2016, 55% in 2017 and 2018, 60% in 2019, and INF-α+RBV+SOF for 12 weeks with the remaining market shares. Every annual cycle a percentage of patients equal to the effectiveness of the antiviral treatment reach a sustained virologic response and during the first year of treatment patients may experience treatment related adverse events. The costs considered (2015) are those of the antiviral therapy, and direct medical costs for health state and adverse events management. Univariate and multivariate sensitivity analyses were performed. RESULTS: DCV would lead to an increase of the costs for the INHS (year 1 +21.31 millions, year 2 +21.35 millions, year 3 + 23.37 millions, year 4 + 23.26 millions and year 5 +16.37 millions). The sensitivity analysis confirmed the robustness of the results. CONCLUSIONS: The use of DCV is likely to have a short term impact on the INHS budget increasing resources use compared to the sole use of INF-α+RBV+SOF. However, a trend of reduction of the costs increase is observed due to the management of health states and adverse events which may lead to the possibility to reduce costs in the long term.